How to Use Indicators for 'Corporatism' in Empirical Applications - Erik Leertouwer; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2002)
There exist many indicators for corporatism. Using a latent variables approach, we extract common aspects in 29 corporatism indicators which have been suggested in the literature and find two factors that can be identified as the degree of coordination between employers and trade unions, and the organizational power of labour. Using these factors in the model of Hall and Franzese (1998) employing data for 16 OECD countries, we find that the organizational power of trade unions does not affect inflation. Likewise, the interaction between central bank independence and coordination does not affect unemployment.
Keywords: 330; corporatism; latent variables; unemployment; inflation